Mozambique and its educational complexities: tensions and resistances in education processes - Juliasse, Arlindo Cornélio Ntunduatha (Práxis Educacional, 2022)
This article problematizes the discussions about tensions and resistances in the Mozambican education processes, seeking to understand how such processes are present in multiple spaces and historical times, taking into account the complexities that characterize the country. The expression spacetime is used in this work to understand that we cannot separate these dimensions when trying to understand everyday life, treating spacetime in a non-dichotomized way. In methodological terms, historical materialism, of Marxist origin, was adopted. To this end, the following categories of method and analysis were listed: contradiction, hegemony and ideology. In the methodological procedures, firstly, the bibliographic research was used, investigating the ideas of several authors and researchers that approach the subject, and secondly, the field research, in which the data collection was carried out through interviews- half structured. Finally, a synthesis of the ideas of the authors and research subjects was made, adding other ideas, articulated with the research objectives and questions. It is a qualitative research of oral history, based on the possibilities of producing knowledge about how subjects in multiple spaces-times become/become readers and writers. The memories of 15 narrators were constituted as oral sources, mediated by vestiges of the past and desires for the future, which give new meaning to the history of education in Mozambique. The research results reveal the re-existence of different contexts in which pedagogical-educational practices occur and the way in which subjects perceive them and establish their relationships.